Design, development and techno economic analysis of novel parabolic trough collector for low-temperature water heating applications. (August 2021) - Upadhyay, Bhargav H.; Patel, Amitkumar J.; Sadasivuni, Kishor Kumar; Mistry, J.M.; Ramana, P.V.; Panchal, Hitesh; Ponnamma, Deepalekshmi; Essa, F.A.
Abstract: The primary objective of this experimentation is to develop and evaluate indigenous PTC capable of producing hot water for low-temperature applications. A new parabolic trough collector is designed; which is easy to accumulate and transport. It allows the easy replacement of receiver pipe, reflector sheet, and heat transfer fluid. The modern design also allows changing the trough's geometrical dimensions. The design has provision for attaching an automatic tracking system and glass cover. This Novel PTC is tested with three different attachments, viz. Manual tracking without glass cover, Manual tracking with glass clover and Automatic tracking without glass cover. Experimental, Optical and Theoretical efficiencies calculated for all three PTC systems. Average experimental efficiency of PTC with Manual tracking, Manual tracking with a Glass cover and Automatic tracking is 11.83%, 13.50%, and 14.94 % respectively. Brief, economic analysis carried out for all three PTC systems. Cost of water heating per kg for manual tracking PTC system is only 0.3/- INR, and for Manual tracking with a Glass cover and Automatic tracking, it is equivalent to 0.4/- INR. The payback period for all is equivalent to 4 years for a PTC system for manual tracking and for PTC systems of Manual tracking with a Glass cover and Automatic tracking it is found equivalent to 5 years. Experimentation conducted in March 2020 at the specific location in Godhra, Gujarat, India.